2019
DOI: 10.1111/papr.12789
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Opioid Use Disorder Among Hospitalized Patients With Chronic Pain

Abstract: Background Patients with chronic pain treated with opioids are at an increased risk for opioid misuse or opioid use disorder (OUD). Recent years have seen a stark increase in abuse, misuse, and diversion of prescription opioid medications. The aim of this study was to investigate trends in changing rates of opioid use disorder among patients with chronic pain. Methods The National Inpatient Sample (NIS) database identified chronic pain admissions with OUD from 2011 to 2015. Patients were identified from the NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Out of the initial 85,329 female patients with newly diagnosed endometriosis, 71.5% were opioid users and 28.5% were non-opioid users. In comparison, patients diagnosed with other diseases reported lower percentages of opioid use: complex regional pain syndrome (7.5%), trauma (13.9%), post-surgical (6.9%), spondylosis (1.8%), failed back surgery syndrome (4.6%), and other chronic pain (7.3%) [30,31]. Another study reported that a third of patients received an opioid prescription within 6 weeks for acute low back pain [31].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Out of the initial 85,329 female patients with newly diagnosed endometriosis, 71.5% were opioid users and 28.5% were non-opioid users. In comparison, patients diagnosed with other diseases reported lower percentages of opioid use: complex regional pain syndrome (7.5%), trauma (13.9%), post-surgical (6.9%), spondylosis (1.8%), failed back surgery syndrome (4.6%), and other chronic pain (7.3%) [30,31]. Another study reported that a third of patients received an opioid prescription within 6 weeks for acute low back pain [31].…”
Section: Discussionmentioning
confidence: 92%
“…The index date for patients with opioid use in this study was their first opioid prescription date after endometriosis diagnosis, while As-Sanie used the endometriosis diagnosis date. It was reported that patients with endometriosis have the highest costs in the first year after diagnosis, partly due to more surgeries in the year after diagnosis [30]. Second, there are prominent differences between the matched populations used for analysis in these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…We included beneficiaries aged ≥18 years with continuous insurance enrollment between December 1, 2017, and December 1, 2018 ( eFigure 1 in the Supplement ). We excluded patients diagnosed with epilepsy 13 , 14 or opioid use disorder (OUD) 15 between December 1, 2017, and December 1, 2018 ( eTable 1 ). We assumed that gabapentinoids and/or opioids were for pain management.…”
Section: Methodsmentioning
confidence: 99%
“…In an effort to understand whether patients were likely to receive opioids because of chronic or outpatient use, we identified the proportion of patients with one of four ICD-10-CM diagnosis codes for chronic pain that have been validated in the literature. (20) We also identified patients with one of 143 opioid-related ICD-10-CM diagnosis codes either for opioid abuse or opioid poisoning, as defined by the AHRQ. (21) seRious opioiD-RelateD aDVeRse eVents…”
Section: Prevalence and Patterns Of Opioid Usementioning
confidence: 99%